2012
DOI: 10.1016/j.trstmh.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Nitazoxanide for the empiric treatment of pediatric infectious diarrhea

Abstract: We conducted a double-blind, placebo-controlled clinical trial to demonstrate the efficacy of nitazoxanide suspension for the treatment of presumed infectious diarrhea in children. Eligible patients must have had diarrheal illness lasting 3-29 days. Patients were randomized to receive either nitazoxanide or placebo twice daily for three days. The primary endpoint was time from first dose to resolution of symptoms. One hundred children mean age 3.3 years were enrolled. The median time to resolution of symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 33 publications
3
34
0
1
Order By: Relevance
“…They found that cooked green banana had a positive impact on the length of hospitalization among all age groups. The impact on diarrhea reduction in treatment group was consistent with the findings of the present study [31]. There was no data of weight changes of participants and the impact on the duration of fever was not consistent with the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…They found that cooked green banana had a positive impact on the length of hospitalization among all age groups. The impact on diarrhea reduction in treatment group was consistent with the findings of the present study [31]. There was no data of weight changes of participants and the impact on the duration of fever was not consistent with the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…In Peru, children receiving empiric nitazoxanide had a shorter duration of diarrhea associated with multiple etiologies compared with those receiving placebo (97). This benefit was also seen in the large group of patients with no identified enteropathogen.…”
Section: Treatmentmentioning
confidence: 99%
“…In a clinical trial, nitazoxanide reduced the duration of diarrheal illness in patients infected with G. intestinalis as well as in those with multiple etiologies or no identified enteropathogen. These results make nitazoxanide particularly suitable for empiric treatment of diarrheal illness in children where the etiology is unknown or presumed to be of infectious origin (Rossignol et al 2012).…”
Section: G Intestinalismentioning
confidence: 99%